Gene Selection Approaches for Classifying Disease Relevant Data Sample - Briso Becky Bell, J; Maria Celestin Vigila, S (International Journal of Engineering and Technology, 2018)
In the latest field of gene expression profiling, the identification of most highly expressed genes with respect to diseases is been in focus lately, As to study the disease types and classify normal from disease syndrome samples. This paper portrays four gene selection approaches such as Pearson correlation, Signal to Noise Correlation, Feature Assessment by Sliding threshold and Feature Assessment by Information Retrieval for retrieving highly relevant genes oriented to a specific disease. This experiment uses various disease dataset for operating on the typical gene selection methods and to select top ten most relevant genes and thus selected genes are learned on using classifiers such as Support Vector Machine, K-Nearest Neighbour and Naïve Bayes to classify the specific disease oriented classes distinctively. Here we also compare the performance of our classifier with the previous papers techniques using classification Accuracy.Â Â